Inkjet printing of thin film transistors - Li, You (2021)
Currently, the fabrication of functional electronic elements by additive manufacturing (AM) is beneficial due to the minimum structural limitations required for this flexible process. As a result, products can be customised and produced to meet the requirements for specific applications, such as in the medical field and automotive industry. However, thus far, only a few varying electronic devices, such as resistors and capacitors, are manufactured by AM technology due to a limited range of processable materials and the insufficient understanding of the fabrication process. Therefore, to broaden the opportunities of printed electronics in academia and industry, it is imperative to investigate a wider range of useable materials and comprehensively understand the AM process. In this thesis, attention is focused on various aspects involved in the fabrication of thin-film transistors (TFTs) by inkjet printing technology, from ink development to product characterisation, and a comprehensive understanding of this process is provided.